Extension Of The Constitutional Court Authority In The Dissolution Of Corrupted Political Parties - Abdul Hakim Siagian (NOMOI Law Review, 2020)
After the amendment of the Constitutionof the Unitary State of the Republic of Indonesia in 1945 changed the constitutional system in Indonesia, since the birth of the Constitutional Court of the Republic of Indonesia which was authorized to adjudicate the dissolution of political parties up to now has never been done by the Constitutional Court, the debate over the dissolution of political parties is also seen as a violation of the rights of political parties. Human rights as the right to assemble and associate, the state administration thought continues to develop about the dissolution of corrupt political parties by giving authority to the Constitutional Court.This research was conducted with normative legal research whose data is sourced from secondary data and since this research data is secondary data, it is included in the type of normative legal research.The nature of this research is descriptive, which aims to provide an overview of social phenomena about the expansion of the authority of the Constitutional Court in the Disbanding of a Corrupt Political Party.Sources of research data in the form of primary legal materials, secondary legal materials and tertiary legal materials.The method of data collection is done using document study techniques, which are analyzed using qualitative analysis techniques.Keywords:Constitutional Court, Disbandment of Political Parties, Corrupt Party.